Influence of surface roughness on silicone rubber voice prostheses on in vitro biofilm formation and clinical lifetime in laryngectomised patients. (19th March 2017) - Buijssen, K.J.D.A.; Oosterhof, J.J.H.; Basil, L.; Waters, M.; Duits, M.A.; Busscher, H.J.; van der Mei, H.C.; van der Laan, B.F.A.M.
Abstract : Objectives: Evaluation of the influence of a smooth surface moulding technique of silicone rubber indwelling voice prostheses on in vitro biofilm formation and analysis of the clinical in situ lifetime. Design: Biofilm formation on smooth and Groningen ultra low resistance (URL) prostheses was studied in an artificial throat model. The clinical lifetime of smooth voice prostheses was compared to the previous lifetime of URL by counting the number of replacements in a consecutive 6‐month period in the same patient. Participants: Eleven laryngectomised patients in follow‐up who required frequent replacement of their voice prostheses. Settings: Tertiary University Medical Center. Results: Use of a smoother mould and less viscous silicone rubber yielded a decrease in surface roughness from 46 to 8 nm and was accompanied by a 40% reduction in the prevalence of bacteria and yeast in in vitro formed biofilms. Clinically, the lifetime was significantly ( P <.005) increased by a factor of 2.1. Conclusions: This combined in vitro and clinical study suggests that the choice of material and in particular its surface finishing may be determining factors with respect to the clinical lifetime of silicone rubber implants and devices failing due to biofilm formation.